Pengaruh Independensi Auditor, Kepemilikan Manajerial, Kualitas Audit, dan Leverage terhadap Integritas Laporan Keuangan (Studi Empiris Pada Perusahaan Sektor Properti & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Rahmaputri, Hafzah; Sugeng, Sugeng (Universitas Batanghari Jambi, 2024)
Financial reports are reports produced from various processes of recording financial transactions within the company. This study aims to determine the effect of auditor independence, managerial ownership, audit quality, and leverage on the integrity of financial statements. This research was conducted on property & real estate sector companies listed on the IDX in 2018-2022. The data used is secondary data obtained from financial reports and annual reports of property & real estate sector companies listed on the IDX for 2018-2022. The final sample size was 164 samples during 2018-2022 with a sampling technique using purposive sampling. This study uses quantitative methods and multiple linear regression models with SPSS version 25. The results show that managerial ownership, audit quality, and leverage have a negative and significant effect on the integrity of financial statements. Meanwhile, auditor independence has no influence on the integrity of financial reports.